1983
DOI: 10.1002/art.1780261111
|View full text |Cite
|
Sign up to set email alerts
|

A new model of osteoarthritis in rabbits

Abstract: A battery of steroidal and nonsteroidal antirheumatic drugs and protease inhibitors were tested by intraarticular injection for effects on osteoarthritis of the knees of rabbits subjected to partial lateral meniscectomy and section of the sesamoid and collateral fibular ligaments. Among the standard drugs, only the glucocorticoid, triamcinolone hexacetonide, and the protease inhibitor, tranexamic acid, exhibited significant anti-osteoarthritic activity. An experimental drug, GPA 2163, also offered some protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…There was no predominance of joint lesions between the lateral and medial tibial compartments in any of the groups ( Table 4 ). In the same way as shown by other studies in the literature, the present study demonstrated that the intra-articular injections of low and high molecular weight glycosaminoglycans and corticosteroid had a protective effect on the chondral bone 5 , 15 , 16 , 17 , 18 . This is also in agreement with the study by Karakurum et al (8) , who compared intra-articular injections of prednisolone with injections of hyaluronic acid, in an experimental osteoarthrosis model in rabbits, and observed that the two drugs administered separately prevented joint degeneration to the same extent, while the effect was boosted when the drugs were administered together.…”
Section: Discussionsupporting
confidence: 90%
“…There was no predominance of joint lesions between the lateral and medial tibial compartments in any of the groups ( Table 4 ). In the same way as shown by other studies in the literature, the present study demonstrated that the intra-articular injections of low and high molecular weight glycosaminoglycans and corticosteroid had a protective effect on the chondral bone 5 , 15 , 16 , 17 , 18 . This is also in agreement with the study by Karakurum et al (8) , who compared intra-articular injections of prednisolone with injections of hyaluronic acid, in an experimental osteoarthrosis model in rabbits, and observed that the two drugs administered separately prevented joint degeneration to the same extent, while the effect was boosted when the drugs were administered together.…”
Section: Discussionsupporting
confidence: 90%
“…Some u-PA and plasmin inhibitors have demonstrated good efficacy in vivo. Transexamic acid [11] and recombinant human protease nexin-1 [12] are active inhibitors of cartilage degradation in animal models, and urinary trypsin inhibitor was reported to be efficacious in human patients with OA [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that the potent effect of glucocorticosteroids on cartilage protection in vitro during concomitant plasminogen/IL-1 stimulation could be due to suppression of u-PA activity. The in vivo efficacy reported for u-PA/plasmin inhibitors [11][12][13] demonstrates the importance of the fibrinolytic system (u-PA/Plasminogen/Plasmin) as an activator of up-regulated pro-MMPs [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several u-PA and plasmin inhibitors have been shown to be effective as potential anti-osteoarthritic agents in vivo. Transexamic acid [42] and recombinant human protease nexin-1 [431 are active inhibitors of degradation in animal models, while urinary trypsin inhibitor was reported to be efficacious in human patients with OA [44].…”
Section: Human Articular Cartilage Explant Datamentioning
confidence: 99%